2017
DOI: 10.1088/1361-6595/aa7587
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally resolved imaging of streamer discharges in air generated in a wire-cylinder reactor with (sub)nanosecond voltage pulses

Abstract: • A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 72 publications
2
40
1
Order By: Relevance
“…We know from our imaging experiments with the nanosecond pulse source [62] that the streamer velocity is higher for a higher applied voltage due to an increased enhanced electric field at the streamer head. This streamer head generates radicals needed for the ozone production, so as long as the streamer propagates, a higher voltage can increase the radical production.…”
Section: Previous Results With the Nanosecond Pulse Sourcementioning
confidence: 91%
See 3 more Smart Citations
“…We know from our imaging experiments with the nanosecond pulse source [62] that the streamer velocity is higher for a higher applied voltage due to an increased enhanced electric field at the streamer head. This streamer head generates radicals needed for the ozone production, so as long as the streamer propagates, a higher voltage can increase the radical production.…”
Section: Previous Results With the Nanosecond Pulse Sourcementioning
confidence: 91%
“…We know from our imaging experiments that the streamers in our corona-plasma reactor are mainly primary streamers [62]. Only somewhere in the range ∆t = 6-9 ns streamers start to cross the gap from the high-voltage wire to the grounded outer cylinder at some points in the reactor at applied voltages of 25 kV and higher (an example, including streamer crossing, is shown in Fig.…”
Section: Pulse Durationmentioning
confidence: 95%
See 2 more Smart Citations
“…To date, there have been many studies on the discharge electrode parameters of coaxial cylindrical electrodes that are used as discharge reactors for general gas processing and also as nanosecond pulsed discharge reactors. [25][26][27][28][29][30] In particular, it has been reported that the internal wire electrode diameter significantly affects the electric field strength near the electrode, and is an extremely important factor in the formation and propagation of streamer discharges. 31 Therefore, elucidating the characteristics of nanosecond pulsed discharge when varying the inner electrode diameter will enable the formation of a discharge suitable for a given use, that is, will enable the formation of a nanosecond pulsed discharge with selectivity.…”
Section: Introductionmentioning
confidence: 99%